MEDICAL THRILLER GENRE IN ENGLISH AND UZBEK LITERATURE: A COMPARATIVE LINGUOPOETIC AND CONCEPTUAL STUDY (International journal of artificial intelligence, 2026)
The medical thriller has emerged as a distinct interdisciplinary literary genre combining medicine, suspense, ethics, and crime. This article provides an extended comparative analysis of the medical thriller genre in English and Uzbek literature. Special attention is given to linguopoetic devices, conceptual frameworks, and cultural specificity. The study applies comparative, conceptual, and linguopoetic methodologies and contributes to international genre studies.